Vitamin D alleviates lipopolysaccharide-induced acute lung injury in mice - LI Xi; ZHAO Yan; WANG Daoxin (Di-san junyi daxue xuebao, 2019)
Objective To investigate the effect of vitamin D on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice and explore the possible mechanism. Methods Forty-five male C57BL/6 mice were randomized equally into control group, LPS group and vitamin D supplement (VD+LPS) group. In VD+LPS group, the mice were given 3 doses of 1, 25(OH)2 vitamin D3 (25 μg/kg) via gavage administrartion at 1, 24 and 48 h before LPS (3 mg/kg) challenge via tracheal intubation, and those in the other 2 groups received lavage with 0.1% dimethylsulfoxide (DMSO) prior to or without LPS challenge. The mice were sacrificed in 2 d after LPS challenge for examination of the total cell count, proportion of neutrophils and protein concentration in the bronchoalveolar lavage fluid (BALF); Enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and IL-17A in the BALF. HE staining was used to observe the pathological changes in the lung tissues, and lung edema was assessed by measuring the wet-to-dry ratio (W/D). Flow cytometry was used to analyze the percentage of T helper 17 (Th17) cells in the lungs. Western blotting and quantitative real-time PCR (qPCR) were performed to detect the expression of retinoic acid-related orphan receptor γt (RORγt) in the lung homogenate. Results Pretreatment of the mice with vitamin D prior to LPS stimulation significantly reduced the severity of LPS-induced lung injury. Compared with those in LPS group, the total cell count, percentage of neutrophils, protein concentration, and levels of IL-6, TNF-α and IL-17A in the BALF were all decreased in VD+LPS group (P < 0.05). The percentage of Th17 cells in the lung tissue and the pulmonary expression of RORγt at both the mRNA and protein levels were significantly lower in VD+LPS group than in LPS group (P < 0.05). Conclusion Vitamin D can alleviate LPS-induced ALI in mice possibly by inhibiting pulmonary inflammatory responses mediated by Th17 cells.